Measuring leadership practice inventory (LPI) among student representative council (SRC) at UiTM Pahang / Musramaini Mustapha, Norulhuda Tajuddin and Wan Kalthom Yahya - Mustapha, Musramaini; Tajuddin, Norulhuda; Yahya, Wan Kalthom (2013)
Students Representative Council (SRC) is a group of students, positioned as student leaders in higher learning institutions. The formation of an SRC in public universities is vital as this has been clearly stated by the Malaysia Ministry of Higher Learning (MOHE) under Act 174 "Akta Institusi - Institusi Pelajaran (Tatatertib) 1976 Seksyen 7 Perkara 3". SRC represents the young voices of university, a council in which leadership qualities are demanded and should be well demonstrated Among the core functions of SRC are to lead the students in materializing the vision and mission of the university, to channel messages between the management and students and to help the university management in handling events involving students. Fundamentally, the SRC is required to have positive thinking as well as a positive image, excellent communication skills, admirable attitude and also pleasant appearance. The main objective of this study is to identify the quantifiable leadership qualities of the present Student Representatives Council (SRC) at UiTM Pahang. This research uses the five 'Leadership Practice Inventory' (LPl) introduced by Kouzes and Posner namely; Model the way, Inspire a shared vision, Challenge the process, Enable others to act, and Encourage the heart. Finally, from the research outcome, this study will suggest the Five Practices of Leadership elements that need to be improved in the future among SRC at UiTM Pahang.